1993
DOI: 10.3382/ps.0720691
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Large Doses of Ascorbic Acid on Performance, Plasma Calcium, Bone Characteristics, and Eggshell Quality in Broilers and Leghorn Hens

Abstract: Four experiments were conducted using broilers (Experiments 1 and 2) or White Leghorn hens (Experiments 3 and 4) to determine the effects of large doses of dietary ascorbic acid on performance, plasma concentration of total and ionic calcium, bone characteristics, and eggshell quality. A total of 564 male broilers were fed diets containing ascorbic acid (ranging from 0 to 3,000 ppm) from 3 to 7 wk of age. Weight gain and feed conversion were measured, and blood plasma was analyzed for total and ionic calcium. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
28
2
5

Year Published

2000
2000
2017
2017

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 24 publications
7
28
2
5
Order By: Relevance
“…The positive effect of citric acid on the bone crude ash was also found in broilers; however, there was no influence of malic acid or fumaric acid (Liem et al 2008). Orban et al (1993) found that the addition of ascorbic acid to the broilers' diet increased the femur breaking strength. In a study on pigs, Radcliffe et al (1998) observed no effect of citric acid supplementation on bone breaking strength, but reported a tendency (P < 0.08) for a linear increase in bone ash content with an increasing content of acid in the diet.…”
Section: Resultsmentioning
confidence: 84%
“…The positive effect of citric acid on the bone crude ash was also found in broilers; however, there was no influence of malic acid or fumaric acid (Liem et al 2008). Orban et al (1993) found that the addition of ascorbic acid to the broilers' diet increased the femur breaking strength. In a study on pigs, Radcliffe et al (1998) observed no effect of citric acid supplementation on bone breaking strength, but reported a tendency (P < 0.08) for a linear increase in bone ash content with an increasing content of acid in the diet.…”
Section: Resultsmentioning
confidence: 84%
“…A porcentagem de cálcio nas cinzas foi influenciada pela fonte de vitamina D, de modo que os maiores valores foram observados com a utilização de colecalciferol. Os valores médios dos diâmetros, interno (0,50 cm) e externo (0,63 cm) das tíbias não foram influenciados pelas fontes de vitamina D e pelos níveis de vitamina C. Embora utilizando níveis de vitamina C bem superiores, Orban et al (1993) trabalharam com suplementação de vitamina C em quantidades que variaram de 1.000 a 3.000 ppm e também não observaram melhora na resistência óssea de tíbias, apesar do significativo aumento linear no conteúdo mineral ósseo e na densidade óssea.…”
Section: Resultsunclassified
“…Vitamin C helps to protect phagocytic cells from oxidative damage (McDowell, 2006). Also, supplemental vitamin C could significantly reduce body temperature (Pardue et al, 1985;Orban et al, 1993). Ascorbic acid supplementation has been shown to have positive effect on mean egg production, egg weight and egg shell thickness (Khan and Sardar, 2005) and on albumen weight, egg length, yolk height and yolk weight (Fayeye et al, 2013) under elevated environmental temperature.…”
Section: Resultsmentioning
confidence: 99%
“…During stresses, either nutritional, environmental, or pathological, the inclusion of vitamin C in birds feed or drinking water appears to alleviate many of the undesirable physical consequences (Whitehead and Keller, 2003;Roussan et al, 2008). Several researchers reported improvement in egg production (Haazele et al, 1991;Fayeye et al, 2013), egg quality (Bell and Marion, 1990), albumen weight (Cheng et al, 1990;Fayeye et al, 2013), egg weight (Elboushy and Van Albada, 1970) and reduction in body temperature (Pardue et al, 1985;Orban et al, 1993) due to supplementing the layers diet with vitamin C under high environmental temperatures. There are reports that 200ppm vitamin C supplementation in feed of poultry raised under heat stress causes significant improvements in live performance, digestibility of nutrients and immune response of the birds (Sahin and Kucuk, 2001;Lohakare et al, 2005).…”
Section: Introductionmentioning
confidence: 99%